2002
DOI: 10.1111/j.1475-2743.2002.tb00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate leaching from organic farms and conventional farms following best practice

Abstract: Abstract. This paper compares nitrate leaching losses from organic farms, which depended on legumes for their nitrogen inputs (66 site years) with those from conventional farms using fertilizers under similar cropping and climatic conditions (188 site years). The conventional farms were within Nitrate Sensitive Areas in England, but sites following special practices associated with that scheme were excluded. Nitrate losses during the organic ley phase (including the winter of ploughing out) were similar (45 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 15 publications
4
36
0
2
Order By: Relevance
“…This might have been a consequence of the lower than average rainfall during the trial period resulting in less drainage than expected for this geographical area. However, in accordance with our results, Stopes et al (2002) reported similar or smaller losses from organically managed sites compared to conventional systems when under similar cropping. In addition, Drinkwater et al (1998) and Bergström & Kirchmann (2004) showed that the inclusion of green manure crops in the cropping sequence can improve soil N retention and, consequently, reduce losses.…”
Section: Effect Of Past and Current Management On Mineral N Leachingsupporting
confidence: 92%
See 2 more Smart Citations
“…This might have been a consequence of the lower than average rainfall during the trial period resulting in less drainage than expected for this geographical area. However, in accordance with our results, Stopes et al (2002) reported similar or smaller losses from organically managed sites compared to conventional systems when under similar cropping. In addition, Drinkwater et al (1998) and Bergström & Kirchmann (2004) showed that the inclusion of green manure crops in the cropping sequence can improve soil N retention and, consequently, reduce losses.…”
Section: Effect Of Past and Current Management On Mineral N Leachingsupporting
confidence: 92%
“…in this study, the amounts of annual n leaching observed (1.3-20 kg ha -1 ) are comparable to those reported in other studies (di & Cameron 2002b;Stopes et al 2002), indicating that addition of n in mineral form had no effect on the leaching patterns nor did incorporation of a leguminous green manure drastically increase mineral N losses. This might have been a consequence of the lower than average rainfall during the trial period resulting in less drainage than expected for this geographical area.…”
Section: Effect Of Past and Current Management On Mineral N Leachingsupporting
confidence: 89%
See 1 more Smart Citation
“…Clearly the optimal use of nitrogenous fertilizers will reduce environmental pollution, however there is little evidence that nitrate leaching differs between organic and conventional production systems when following best practice (Stopes et al 2002;Trewavas 2002). Our results suggest that at the level of gene expression, wheat grain from plants supplied with either organic or inorganic nitrogen is reproducibly different.…”
Section: Resultsmentioning
confidence: 99%
“…It is also quite common to base leaching estimates on nutrient concentrations obtained from soil water samples in porous suction probes and water flux calculations with mathematical simulation models (e.g. Stopes et al, 2002), which also generates uncertain load estimates. Another limitation of a number of leaching studies is that leaching loads are only related to the cropping area, disregarding yield differences (Corré et al, 2003;Kirchmann and Bergström, 2001), which can lead to erroneous conclusions about the environmental benefits of organic systems (e.g.…”
Section: Introductionmentioning
confidence: 99%